Angola : First Review Under the Stand-By Arrangement and Request for a Modification of a Performance Criterion. (IMF Staff Country Reports; Country Report ;, 2010)
This paper discusses key findings of the First Review Under the Stand-By Arrangement for Angola. The paper reveals that the authorities' reforms are beginning to bear fruit in terms of achieving key program goals. The heavy foreign exchange market pressures that were evident at the program negotiations stage (September 2009) have eased. The reintroduction of the foreign exchange auction system has led to a significant and orderly adjustment in the official rate, and together with a modest appreciation of the parallel rate, has narrowed the spread between the two markets.